2020
DOI: 10.1016/j.acuroe.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

What has changed during the state of emergency due to COVID-19 on an Academic Urology Department of a Tertiary Hospital in Portugal

Abstract: Objective To compare the activity the Urology Department of a Portuguese Academic Hospital during the state of emergency and the equivalent period at the previous year. We compared the number of elective consultations and diagnostic urologic examinations, number and type of elective surgeries, as well as patients’ demographic characteristics and main causes of presentation to Urology Emergency Department (ED) during the two mentioned periods. Materials and methods Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Decreases in health care utilization during the COVID-19 pandemic have been reported in different health care systems and settings. Findings include decreases in consultations to emergency departments [ 5 , 8 , 11 ], psychiatric emergency consultations and number of admissions to psychiatric clinics [ 7 , 10 ], visits from patients living with HIV [ 16 ], non-urgent and surgical ophthalmologic care [ 9 ], urologic examinations [ 6 ], first diagnoses of diabetes and circulatory system diseases [ 17 ], hospitalization for a range of diagnoses [ 18 ], as well as different types of preventive and elective care (e.g. mammograms, colonoscopies) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in health care utilization during the COVID-19 pandemic have been reported in different health care systems and settings. Findings include decreases in consultations to emergency departments [ 5 , 8 , 11 ], psychiatric emergency consultations and number of admissions to psychiatric clinics [ 7 , 10 ], visits from patients living with HIV [ 16 ], non-urgent and surgical ophthalmologic care [ 9 ], urologic examinations [ 6 ], first diagnoses of diabetes and circulatory system diseases [ 17 ], hospitalization for a range of diagnoses [ 18 ], as well as different types of preventive and elective care (e.g. mammograms, colonoscopies) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys have demonstrated that COVID-19 has had a large impact on resident surgical education in the US 4,12 Italy, 3,16,[23][24] France, 6,25 and Portugal. 26 However, despite the differences in baseline residency characteristics, governmental responses to the pandemic, and timing of peak caseloads, no studies to our knowledge have directly assessed how these changes have impacted residents across the globe. 1,27 Of note, the surveyed countries are all categorized as high income countries heavily affected by the early initial peak in COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%